Discovery of 6-Diazo-5-oxo-l-norleucine (DON) Prodrugs with Enhanced CSF Delivery in Monkeys: A Potential Treatment for Glioblastoma - Rais, Rana; Jančařík, Andrej; Tenora, Lukáš; Nedelcovych, Michael; Alt, Jesse; Englert, Judson; Rojas, Camilo; Le, Anne; Elgogary, Amira; Tan, Jessica; Monincová, Lenka; Pate, Kelly; et al. (Journal of medicinal chemistry, 2016)
The glutamine antagonist 6-diazo-5-oxo-l-norleucine (DON, 1) has shown robust anticancer efficacy in preclinical and clinical studies, but its development was halted due to marked systemic toxicities. Herein we demonstrate that DON inhibits glutamine metabolism and provides antitumor efficacy in a murine model of glioblastoma, although toxicity was observed. To enhance DON's therapeutic index, we utilized a prodrug strategy to increase its brain delivery and limit systemic exposure. Unexpectedly, simple alkyl ester-based prodrugs were ineffective due to chemical instability cyclizing to form a unique diazo-imine. However, masking both DON's amine and carboxylate functionalities imparted sufficient chemical stability for biological testing. While these dual moiety prodrugs exhibited rapid metabolism in mouse plasma, several provided excellent stability in monkey and human plasma. The most stable compound (5c, methyl-POM-DON-isopropyl-ester) was evaluated in monkeys, where it achieved 10-fold enhanced cerebrospinal fluid to plasma ratio versus DON. This strategy may provide a path to DON utilization in glioblastoma multiforme patients.
Keywords: Animals; Antimetabolites, Antineoplastic; Female; Prodrugs; ženské pohlaví; Mice, Nude; glutamin; nádory mozku; lidé; Mice; Diazooxonorleucine; prekurzory léčiv; myši; glioblastom; Glutamine; Glioblastoma; Haplorhini; Haplorrhini; protinádorové antimetabolity; Brain Neoplasms; zvířata; myši nahé; diazooxonorleucin; Humans